2021
DOI: 10.1049/nbt2.12048
|View full text |Cite
|
Sign up to set email alerts
|

Responses of bimetallic Ag/ZnO alloy nanoparticles and urea on morphological and physiological attributes of wheat

Abstract: Wheat (Triticum aestivum L.) is the most important staple food crop globally. According to economic survey 2018-19, agriculture sector of Pakistan grew by 0.85%, with wheat accounting for 8.9% of agriculture and 1.6% of GDP, and its production fell short of the target by 4.9%. Wheat requires beneficial ties to improve its efficiency with the help of modern technology. Nanotechnology modifies conventional agricultural practices as these are stimulating agents for plant growth. Green bimetallic Ag/ZnO alloy nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Absorption peaks were in high wavelength region, which clearly suggested the formation of bimetallic Ag-ZnO NPs. Similarly, 2 peaks for Ag/ZnO bimetallic NPs were measured between 330 nm and 366-379 nm, confirming the formation of bimetallic Ag/ZnO alloy NPs from Moringa oleifera leaf extract [31].…”
Section: Characterization Of Uv-mediated Green Synthesized Agnps Znonps and Bimetallic Ag-znonps 221 Uv-visible Spectroscopysupporting
confidence: 58%
“…Absorption peaks were in high wavelength region, which clearly suggested the formation of bimetallic Ag-ZnO NPs. Similarly, 2 peaks for Ag/ZnO bimetallic NPs were measured between 330 nm and 366-379 nm, confirming the formation of bimetallic Ag/ZnO alloy NPs from Moringa oleifera leaf extract [31].…”
Section: Characterization Of Uv-mediated Green Synthesized Agnps Znonps and Bimetallic Ag-znonps 221 Uv-visible Spectroscopysupporting
confidence: 58%
“…Therefore, it can be proposed that by using urea nanoparticles, the direct uptake of NH 4 + can speed up its entry into the glutamine cycle by circumventing the conversion from N-NO 3 − . Such increases in fresh-weights have been reported previously on sweet corn using urea provided with vermicompost and azocompost [48], wheat using bimetallic silver/zinc oxide nanocomposite with urea [49], and urea embedded in nanocellulose [50], and rice using urea phosphate [51].…”
Section: Early Effects Of Tnu On Seedling Germination and Growthsupporting
confidence: 75%
“…Prior research underscores the pivotal role of Ag and ZnO NPs in expediting leaf expansion, curtailing leaf senescence and thylakoid lamellae damage, thereby fostering advanced chlorophyll- a and b biosynthesis processes in plants 90 . Ehsan et al 91 reported analogous findings, detailing significant upticks of 92% in chlorophyll- a , 71% in chlorophyll- b , and 84% in total chlorophyll in wheat when exposed to 100 mg/L urea and 75 mg/L bimetallic Ag/ZnO alloy NPs. In concurrence with our observations, the studies of Sharma et al 92 and Sun et al 93 ascertain that Ag and ZnO NPs orchestrate gene expressions that encode regulatory enzymes within the photosynthesis process, consequently fostering substantial enhancements in total chlorophyll content.…”
Section: Resultsmentioning
confidence: 72%